Government intervention in the economy: a comparative analysis of Singapore and Hong Kong - Lam, Newman M.K. (2000)
Singapore and Hong Kong are very different and yet very similar in many respects. A study of their current profiles and historical development indicates that the two have achieved comparable economic successes through different development strategies. After World War II, Singapore gained political independence while Hong Kong achieved economic restructuring. The Singapore government adopted an interventionist approach to develop its economy, while the Hong Kong government followed the laissez-faire principle. However, as the two were maturing socially and economically in the last few decades, both governments found the necessity to adopt a hybrid strategy of mixing economic interventions with the free-market approach. An examination of public finance and economic policies since the onset of the Asian economic turmoil shows that the two have become increasingly similar in their economic approaches, with heavy emphasis on stabilizing the economy and stimulating business activities through government initiatives. Based on their projected economic, social and political development, the Hong Kong government is expected to become more interventionist while its Singapore counterpart is expected to go in the opposite direction. The economic development strategies of the two governments, coming from two extremes, will become more alike in the foreseeable future, for reasons of political feasibility in the former. - Reproduced
Keywords: Economic and social development - Hong Kong; Economic and social development - Singapore; Economic and social development